1989
DOI: 10.1007/bf02926482
|View full text |Cite
|
Sign up to set email alerts
|

Microradiographic demonstration of human intrarenal microlymphatic pathways

Abstract: Renal lymphatics play a prominent role in physiological and pathologic states. However, intrarenal microlymphatic morphology has not been well established in humans. We have developed microangiographic techniques for studying microlymphatic morphology. Lymphatics were identified by location, presence of valves, and histologic characteristics in 4 patients (3 presented here and 1 reported previously), all of whom had congestive cardiac states. The renal lymphatics begin in the cortical interstitium near glomeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 10 publications
2
26
1
Order By: Relevance
“…Thus, neolymphangiogenesis could be detrimental if the immune process is perpetuated and augmented in the inflammed tissues, but it may be beneficial if cytotoxic cells are removed more efficiently. In kidney grafts, the newly formed lymphatics reach deep into the tubulointerstitial space, unlike in normal kidneys (Cuttino et al, 1989), and are associated with nodular infiltrates that can be found in 10%-15% of transplant biopsies. As apoptosis can only partially remove infiltrates at a rate similar to the one in the thymus, lymph vessels could be responsible for the residual evacuation (Paavonen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, neolymphangiogenesis could be detrimental if the immune process is perpetuated and augmented in the inflammed tissues, but it may be beneficial if cytotoxic cells are removed more efficiently. In kidney grafts, the newly formed lymphatics reach deep into the tubulointerstitial space, unlike in normal kidneys (Cuttino et al, 1989), and are associated with nodular infiltrates that can be found in 10%-15% of transplant biopsies. As apoptosis can only partially remove infiltrates at a rate similar to the one in the thymus, lymph vessels could be responsible for the residual evacuation (Paavonen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This ''second circulation'' network is also present in the kidney, where the lymph vessels are confined to the area around largeand middle-sized arteries (McIntosh and Morris, 1971) in the cortex, but do not appear in the peritubular space (Kerjaschki et al, 2004). The medulla of a healthy person rarely possesses any lymphatics (Cuttino et al, 1989). Just a few years ago, the Kerjaschki group showed that neolymphangiogenesis occurs in allograft kidney transplants, a finding confirmed by another report 3 years later (Adair et al, 2007;Stuht et al, 2007).…”
mentioning
confidence: 99%
“…Hydraulic permeability (L p ) relates the total flux of solvent (water) plus solute through a membrane (volume flux, J v ) to the difference in hydrostatic pressure between the two sides of the membrane (⌬P). L p equals (J v /⌬P), when the transmembrane dif- 14 C]urea permeability (PU, ordinate) vs. 22 Na permeability (PNa, abscissa) is shown for outer medullary DVR (OMDVR) isolated from Sprague-Dawley rats and perfused in vitro and inner medullary DVR and AVR (IMDVR, IMAVR) perfused on the surface of the exposed papilla of MunichWistar rats in vivo. Dashed line represents identity.…”
Section: Transport Properties-general Definitionsmentioning
confidence: 99%
“…Evidence for a shared pathway conducting diffusion of hydrophilic solutes through the walls of DVR comes from measurements of the correlations between the diffusional permeabilities of these microvessels to 22 Na (P Na ) and to tritiated water (P D ), (90). The simplest interpretation of correlated variations in diffusional permeability to hydrophilic solutes is that they arise from variations in a shared aqueous (porous) pathway.…”
Section: Transport Of Water Through the Dvr Wallmentioning
confidence: 99%
See 1 more Smart Citation